Tear-resistant aramid nano insulation paper as well as preparation method and application thereof

Through multiple forming and high-temperature and high-pressure hot-pressure treatment, aramid nano-insulated paper with high tear and dielectric strength was prepared, which solved the tear and dielectric strength of aramid nano-insulated paper in the prior art. The problem of low results enables more efficient and reliable electrical insulation performance.

CN119434017AActive Publication Date: 2025-02-14SHAANXI UNIV OF SCI & TECH
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411343558.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2025-02-14
Estimated Expiration
2044-09-25

AI Technical Summary

Technical Problem

Existing aramid nano-insulated papers are prone to tear under external forces and have low dielectric strength, making it difficult to meet the application needs of high-end electrical insulation.

Method used

By preparing para-aramid nanofiber aqueous dispersion and meta-aramid chopped fiber aqueous dispersion, multiple forming methods are used to form aramid nanoinsulating paper with dense structure and high strength, and hot pressure is passed through high temperature and high pressure Treatment improves paper tightness and tear.

Benefits of technology

It significantly improves the tear and dielectric strength of aramid nano-insulated paper, enhances the bonding force between fibers, improves the overall performance of insulated paper, and is suitable for high-end electrical insulation fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119434017A_ABST
    Figure CN119434017A_ABST
Patent Text Reader

Abstract

The invention provides tear-resistant aramid nano insulation paper as well as a preparation method and application thereof. The tear-resistant aramid nano insulation paper is prepared from multi-scale compounded meta-aramid chopped fibers with high elongation and good rigidity and para-aramid nanofibers with a unique nanoscale structure, rich functional groups and excellent mechanical properties through secondary forming and hot pressing. The excellent film-forming property of the para-aramid nanofibers and the advantage that rich functional groups on the surfaces of the para-aramid nanofibers and the meta-aramid chopped fibers can easily generate a strong network cross-linked structure are fully exerted, and the novel aramid paper-based insulating material with high tearability and high dielectric strength is developed. The defects of stress concentration damage, poor dielectric strength and the like caused by easy tearing of the existing aramid nano insulation paper are overcome, and the aramid nano insulation paper can be used as an ultrathin insulation layer to be applied to the next generation of highly lightweight and integrated special electrical equipment to realize miniaturization, integration and structural weight reduction of the equipment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of aramid paper-based insulating materials, and in particular to tear-resistant aramid nano insulating paper and a preparation method and application thereof. Background Art

[0002] At present, aramid paper-based insulation materials are developing rapidly and are mainly used as the main insulation materials for turns, phases, windings and wire ends of large electrical equipment such as high-power dry-type transformers, oil-immersed transformers, special motors for mining, traction motors for high-speed trains, wind turbines, and ultra-high voltage transformers. However, traditional aramid paper-based insulation materials are still mainly made of macroscopic aramid chopped, precipitated or pulp fibers. Due to the single morphology of macroscopic aramid fibers, smooth and hydrophobic surface, and high inertness, the prepared traditional aramid paper-based insulation materials have loose structures, weak interface bonding, low mechanical strength and dielectric strength, and are difficult to meet the application needs of high-end fields.

[0003] Aramid Nanofibers (ANFs) retain most of the properties of macroscopic aramid fibers, including thermal stability and high crystallinity. At the same time, the rich active groups, large aspect ratio and specific surface area on the surface of aramid nanofibers give them excellent properties of nanomaterials, bringing them mechanical and optical properties that conventional macroscopic aramid fibers cannot achieve. In addition, aramid nanofibers can form a cross-linked network structure through strong hydrogen bonds, and have excellent paper-forming properties. The paper has the advantages of high strength, high temperature resistance, transparency and good flexibility, and has great application prospects in the field of electrical insulation materials. Aramid nano insulation paper is made of aramid nanofibers as raw materials through wet forming or sol-gel phase transformation. It has excellent dielectric strength and tensile strength, extremely thin thickness, and excellent high temperature resistance. It has broad application prospects in the field of advanced electrical insulation. However, since the diameter of aramid nanofibers is about 10-15 nm and the length is short, only 3~5μm, the physical interlacing and mechanical bonding between the fibers are weak, and they are easily torn under the action of external forces, especially when there are gaps. This poses a great safety hazard to its future application in the field of high-end electrical insulation.

[0004] The manufacturing process of the existing aramid nano-insulating paper mainly involves mixing different types of meta-aramid fibers in different proportions, and making and drying the mixed fiber dispersion. Invention patent CN109468882A proposes a method in which pretreated aramid short fibers and para-aramid pulp fibers are modified with a coupling agent or a coupling agent solution, made into paper, and the paper is gradient-structured with nano para-aramid fibers to obtain gradient-structured nano-aramid paper. However, the distribution of the nano-aramid fibers in the paper structure is uneven, resulting in low dielectric strength. Invention patent CN112609493A proposes a method in which conventional short fibers and pulp or precipitated fibers are used to make meta- or para-aramid, para-aramid nano-fiber composite wet paper sheets, and then the para-aramid nano-fiber dispersion is sprayed or sizing on the surface of the wet paper sheets, and then compounded and dried to form nano-reinforced aramid paper. Although this method enhances the strength of the aramid paper, the papermaking process is complicated and the dielectric strength of the paper is still low. Summary of the invention

[0005] The purpose of the present invention is to provide a tear-resistant aramid nano-insulating paper and a preparation method and application thereof, so as to overcome the problems existing in the prior art, provide a tear-resistant aramid nano-insulating paper and a preparation method thereof with simple raw materials, excellent product performance and high dielectric strength, improve the defects of the current insulating paper-based materials such as easy stress concentration breakage and low dielectric strength; at the same time, it can also be used as an ultra-thin insulating layer in the next generation of highly lightweight and integrated special electrical equipment, realize equipment miniaturization, integration and structural weight reduction, and promote the development of modern compact lightweight electrical insulation equipment towards a more efficient and reliable direction.

[0006] To achieve the above purpose, the technical solution of the present invention is as follows: A method for preparing tear-resistant aramid nano insulating paper comprises the following specific steps: (1) Preparing a para-aramid nanofiber aqueous dispersion: injecting deionized water into a para-aramid nanofiber (PPTA) dispersion in a dimethyl sulfoxide (DMSO), potassium hydroxide (KOH) and deionized water (H2O) system under high pressure while stirring, and then washing with deionized water under vacuum filtration until it becomes a gel, thereby obtaining a para-aramid nanofiber aqueous dispersion A dispersed in deionized water; diluting the para-aramid nanofiber aqueous dispersion A, and then dispersing by dispersing and stirring to obtain a para-aramid nanofiber aqueous dispersion B; (2) Preparing a meta-aramid chopped fiber aqueous dispersion: dispersing meta-aramid chopped fibers of different lengths in water, adding a dispersant, and then dispersing by dispersing and stirring to obtain a meta-aramid chopped fiber aqueous dispersion C; (3) Papermaking the meta-aramid chopped fiber aqueous dispersion C obtained in (2) to obtain a loose, porous insulating paper matrix; the basis weight of the insulating paper matrix is ​​3-30 g / m2 ; (4) The para-aramid nanofiber aqueous dispersion B obtained in (1) is subjected to secondary forming and papermaking on the insulating paper substrate obtained in (3) to obtain aramid nano-insulating paper; the aramid nano-insulating paper has a basis weight of 30-60 g / m 2 , wherein the mass ratio of para-aramid nanofiber to meta-aramid short-cut fiber is 50~90:10~50; (5) further pressing, drying, and hot pressing the aramid nano-insulating paper obtained in (4) to obtain tear-resistant aramid nano-insulating paper; Furthermore, the preparation method of the para-aramid nanofiber dispersion (ANFs) in the dimethyl sulfoxide, potassium hydroxide and deionized water system in (1) is as follows: para-aramid chopped fibers, potassium hydroxide, dimethyl sulfoxide and deionized water are mixed in proportion and sealed, and then stirred at a speed of 1200-1500 r / min for 2-4 h to obtain a para-aramid nanofiber dispersion with a concentration of 5-15 mg / mL; the diameter of the para-aramid nanofibers in the para-aramid nanofiber dispersion is 8-15 nm and the length is 3-8 μm; Furthermore, in said (1), the speed of stirring the para-aramid nanofiber dispersion in the dimethyl sulfoxide, potassium hydroxide and deionized water system is 1000-1500 r / min; Furthermore, in said (1), the para-aramid nanofiber aqueous dispersion A is dispersed and stirred for 20000-30000r; the mass concentration of said para-aramid nanofiber aqueous dispersion B is 0.05-0.12%; Furthermore, the ratio of the meta-aramid short fibers of different lengths in (2) is 10-30:30-50:30-50 by weight of meta-aramid short fibers: meta-aramid short fibers; the length of the meta-aramid short fibers is 4-6 mm, the length of the meta-aramid short fibers is 7-9 mm, and the length of the meta-aramid short fibers is 10-12 mm. Furthermore, the dispersing, stirring and dispersing in (2) is performed for 20,000 to 30,000 rpm; the mass concentration of the meta-aramid chopped fiber aqueous dispersion C is 0.05 to 0.12%; Furthermore, the (3) is specifically as follows: the meta-aramid chopped fiber aqueous dispersion C obtained in (2) is paper-made on a 200-400 mesh forming net to obtain a loose and porous insulating paper matrix; Furthermore, the pressing and drying in (5) are carried out using conventional papermaking processes, with a hot pressing temperature of 230-245°C, a hot pressing pressure of 10-15 MPa, and a hot pressing time of 5-10 min; A tear-resistant aramid nano-insulating paper is obtained based on the preparation method of the tear-resistant aramid nano-insulating paper according to any one of the above claims.

[0007] An application of the tear-resistant aramid nano-insulation paper as an ultra-thin insulation layer in the field of next-generation highly lightweight and integrated special electrical equipment.

[0008] The above technical solution has the following advantages or beneficial effects: The invention provides a method for preparing tear-resistant aramid nano-insulating paper, wherein meta-aramid chopped fibers are used as a skeleton matrix structure, and para-aramid nano-fibers with unique nano-scale structure, high strength and high modulus, high specific surface area, high aspect ratio, and excellent temperature resistance are used as coating and filling materials for the meta-aramid chopped fiber skeleton structure, and micro / nano rough combination is constructed on the smooth surface of the aramid chopped fibers to overcome the problems of smooth surface, strong inertness, and few active groups of the chopped fibers, improve the defects of the current insulating paper-based materials such as easy stress concentration breakage and low dielectric strength, and enhance the bonding force between fibers; the entire manufacturing process of the invention has the characteristics of simple raw materials and excellent product performance, and the aramid nano-insulating paper obtained by multiple forming of meta-aramid chopped fibers and para-aramid nano-fibers of different dimensions has the characteristics of tear resistance, high temperature resistance, flame retardancy, high dielectric strength, and the like.

[0009] Furthermore, a secondary forming method is used for papermaking. Different lengths of meta-aramid chopped fibers are compounded to form the skeleton matrix structure of the insulation paper, and fibers of different lengths are interwoven to enhance the mechanical strength of the fibers; then the para-aramid nanofibers are vacuum filtered on the meta-aramid chopped fiber skeleton matrix structure, and the aramid nanofibers are filled in the loose and porous skeleton matrix structure, so that the surface of the meta-aramid chopped fibers is evenly coated to form a dense film, forming a structure similar to reinforced concrete. This secondary forming papermaking method not only improves the tear resistance of the insulation paper, but also prevents the loss of nanofibers.

[0010] Furthermore, high temperature and high pressure hot pressing is used to soften the meta-aramid chopped fibers, achieve deformation and migration between the fibers, fill the pores between the fibers, and make the insulating paper have a dense aramid nano-layered structure with composite meta-aramid chopped fibers of different lengths in between; this process significantly improves the tightness and tear resistance of the aramid nano-insulating paper and makes the paper surface smoother.

[0011] The present invention provides a tear-resistant aramid nano-insulation paper, the tear strength of which is 13 to 29 times higher than that of a pure aramid nano-film. The aramid nano-insulation paper can also achieve thinning of the insulation layer and high tearing performance while ensuring excellent insulation performance.

[0012] The present invention provides an application of tear-resistant aramid nano-insulating paper as an ultra-thin insulating layer in the field of next-generation highly lightweight and integrated special electrical equipment, such as electrical equipment in 5G communication power systems, rail transit, new energy vehicles and other fields. It can effectively solve the problems of poor active heat dissipation and short service life of electrical equipment due to low thermal conductivity of insulating paper, realize equipment miniaturization, integration and structural weight reduction, and promote the development of modern compact and lightweight electrical insulation equipment towards a more efficient and reliable direction. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 This is a process flow chart of a method for preparing tear-resistant aramid nano insulating paper of the present invention; FIG. 2( a ) is a scanning electron microscope image of the surface of the aramid nano-insulating paper obtained in Example 4 of the present invention, and FIG. 2( b ) is a partially enlarged scanning electron microscope image of the surface of the aramid nano-insulating paper obtained in Example 4 of the present invention; Figure 3 This is a scanning electron microscope image of the cross section of the aramid nano-insulation paper obtained in Example 4 of the present invention; FIG. 4( a ) is a scanning electron microscope image of the breakdown point of the aramid nano-insulation paper obtained in Example 4 of the present invention, and FIG. 4( b ) is a locally enlarged scanning electron microscope image of the breakdown point of the aramid nano-insulation paper obtained in Example 4 of the present invention. DETAILED DESCRIPTION

[0014] The present invention is further described in detail below in conjunction with specific embodiments, which are intended to explain the present invention rather than to limit it. In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention. It should be noted that the terms "first", "second", etc. in the specification and claims of the present invention and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present invention described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.

[0015] A method for preparing tear-resistant aramid nano-insulation paper, see Figure 1 , including the following specific steps: (1) preparing a para-aramid nanofiber aqueous dispersion: injecting deionized water into a para-aramid nanofiber dispersion in a system of dimethyl sulfoxide, potassium hydroxide and deionized water under high pressure while stirring, and then washing with deionized water under vacuum filtration until it becomes a gel, thereby obtaining a para-aramid nanofiber aqueous dispersion A dispersed in deionized water; diluting the para-aramid nanofiber aqueous dispersion A, and then dispersing by dispersing and stirring to obtain a para-aramid nanofiber aqueous dispersion B; (2) Preparing a meta-aramid chopped fiber aqueous dispersion: dispersing meta-aramid chopped fibers of different lengths in water, adding a dispersant to prevent fiber flocculation, and then dispersing by dispersing and stirring to obtain a meta-aramid chopped fiber aqueous dispersion C; (3) The meta-aramid chopped fiber aqueous dispersion C obtained in (2) is paper-made to obtain a loose and porous insulating paper matrix, and the paper basis weight of the insulating paper matrix is ​​3-30 g / m 2 ; Aramid nanofibers are filled in the loose and porous skeleton matrix structure to form a structure similar to reinforced concrete. This secondary forming papermaking method not only improves the tearing strength of the insulating paper, but also prevents the loss of nanofibers; (4) The para-aramid nanofiber aqueous dispersion B obtained in (1) is subjected to secondary forming and papermaking on the insulating paper substrate obtained in (3) to obtain aramid nano-insulating paper; the aramid nano-insulating paper obtained has a paper weight of 30-60 g / m 2 , wherein the mass ratio of para-aramid nanofiber to meta-aramid short-cut fiber is 50~90:10~50; (5) The aramid nano-insulating paper obtained in (4) is further pressed, dried, and hot-pressed to obtain tear-resistant aramid nano-insulating paper; high temperature and high pressure hot pressing is used to soften the meta-aramid chopped fibers by heat, thereby achieving deformation and migration between the fibers and filling the pores between the fibers, so that the insulating paper has a dense aramid nano-layered structure and has composite meta-aramid chopped fibers of different lengths therein; this process significantly improves the tightness and tear resistance of the aramid nano-insulating paper and makes the surface of the paper smoother; Preferably, the preparation method of the para-aramid nanofiber dispersion in the dimethyl sulfoxide, potassium hydroxide and deionized water system in (1) is: para-aramid chopped fibers, potassium hydroxide, dimethyl sulfoxide and deionized water are mixed in proportion and sealed, and then stirred at a speed of 1200-1500 r / min for 2-4 h to obtain a para-aramid nanofiber dispersion with a concentration of 5-15 mg / mL; the diameter of the para-aramid nanofibers in the para-aramid nanofiber dispersion is 8-15 nm and the length is 3-8 μm; Preferably, in said (1), the speed of stirring the para-aramid nanofiber dispersion in the dimethyl sulfoxide, potassium hydroxide and deionized water system is 1000-1500 r / min; Preferably, in said (1), the para-aramid nanofiber aqueous dispersion A is dispersed and stirred for 20000-30000 r; the mass concentration of said para-aramid nanofiber aqueous dispersion B is 0.05-0.12%; Preferably, the ratio of the meta-aramid chopped fibers of different lengths in (2) is 10-30:30-50:30-50 by weight; the length of the meta-aramid chopped fibers is 4-6 mm, the length of the meta-aramid chopped medium-long fibers is 7-9 mm, and the length of the meta-aramid chopped long fibers is 10-12 mm; the fibers of different lengths are interwoven to enhance the mechanical strength of the paper; Preferably, the dispersing stirring and dispersion in (2) is 20000-30000 r; the mass concentration of the meta-aramid chopped fiber aqueous dispersion C is 0.05-0.12%; Preferably, the step (3) is as follows: papermaking the meta-aramid chopped fiber aqueous dispersion C obtained in step (2) on a 200-400 mesh forming net to obtain a loose and porous insulating paper matrix; Preferably, the drying in (5) is carried out using a conventional papermaking process, with a hot pressing temperature of 230-245°C, a hot pressing pressure of 10-15 MPa, and a hot pressing time of 5-10 min.

[0016] A tear-resistant aramid nano-insulating paper is obtained based on the preparation method of the tear-resistant aramid nano-insulating paper according to any one of the above claims.

[0017] An application of the above-mentioned tear-resistant aramid nano-insulating paper as an ultra-thin insulating layer in the field of next-generation highly lightweight and integrated special electrical equipment, such as electrical equipment in 5G communication power systems, rail transit, new energy vehicles and other fields, can effectively solve the problems of poor active heat dissipation and short service life of electrical equipment due to low thermal conductivity of insulating paper, realize equipment miniaturization, integration and structural weight reduction, and promote the development of modern compact and lightweight electrical insulation equipment towards a more efficient and reliable direction.

[0018] The present invention is further described in detail below in conjunction with specific embodiments, which are intended to explain the present invention rather than to limit it.

[0019] Embodiment 1: A method for preparing tear-resistant aramid nano-insulating paper in this embodiment specifically comprises the following steps: (1) Para-aramid chopped fibers, potassium hydroxide, dimethyl sulfoxide and deionized water are mixed in proportion and sealed, and rapidly stirred at 1200 r / min for 2 h to obtain a para-aramid nanofiber dispersion with a concentration of 8 mg / mL; the diameter of the para-aramid nanofibers in the para-aramid nanofiber dispersion is 8-15 nm and the length is 3-8 μm; then, deionized water is injected into the para-aramid nanofiber dispersion under high pressure under the stirring action of 1000 r / min, and then washed with deionized water under vacuum filtration until it is in a gel state, to obtain a para-aramid nanofiber aqueous dispersion A dispersed in deionized water; the para-aramid nanofiber aqueous dispersion A is diluted, and then dispersed by dispersing stirring for 20000 r to obtain a para-aramid nanofiber aqueous dispersion B with a mass concentration of 0.05%; (2) Dispersing meta-aramid chopped short fibers: meta-aramid chopped medium and long fibers: meta-aramid chopped long fibers in water at a ratio of 10:30:60, adding a dispersant for dispersion, and then dispersing by stirring for 20,000 r to obtain a meta-aramid chopped fiber aqueous dispersion C with a mass concentration of 0.1%; (3) The meta-aramid chopped fiber aqueous dispersion C obtained in (2) is paper-made on a 200-mesh forming net to obtain a loose, porous insulating paper substrate; the paper basis weight of the insulating paper substrate obtained is 4.1 g / m 2 ; (4) secondary forming and papermaking the para-aramid nanofiber aqueous dispersion B obtained in (1) on the insulating paper substrate obtained in (3) to obtain aramid nano insulating paper; (5) The aramid nano-insulating paper obtained in (4) is further pressed, dried, and hot-pressed to obtain tear-resistant aramid nano-insulating paper; the drying is carried out using a conventional papermaking process; the hot-pressing temperature is 235°C, the hot-pressing pressure is 10 MPa, and the hot-pressing time is 8 min; the mass ratio of para-aramid nanofibers to meta-aramid short fibers in the tear-resistant aramid nano-insulating paper is 90:10; the prepared paper has a basis weight of 41 g / m 2 .

[0020] Embodiment 2: A method for preparing tear-resistant aramid nano-insulating paper in this embodiment specifically comprises the following steps: (1) Para-aramid chopped fibers, potassium hydroxide, dimethyl sulfoxide and deionized water are mixed in proportion and sealed, and rapidly stirred at 1300 r / min for 2.5 h to obtain a para-aramid nanofiber dispersion with a concentration of 10 mg / mL; the diameter of the para-aramid nanofibers in the para-aramid nanofiber dispersion is 8-15 nm and the length is 3-8 μm; then, deionized water is injected into the para-aramid nanofiber dispersion under high pressure under the stirring action of 1200 r / min, and then washed with deionized water under vacuum filtration until it is in a gel state, to obtain a para-aramid nanofiber aqueous dispersion A dispersed in deionized water; the para-aramid nanofiber aqueous dispersion A is diluted, and then dispersed by dispersing stirring for 25000 r to obtain a para-aramid nanofiber aqueous dispersion B with a mass concentration of 0.1%; (2) Dispersing meta-aramid chopped short fibers: meta-aramid chopped medium and long fibers: meta-aramid chopped long fibers in water at a ratio of 20:30:50, adding a dispersant for dispersion, and then dispersing by stirring for 25000 r to obtain a meta-aramid chopped fiber aqueous dispersion C with a mass concentration of 0.05%; (3) The meta-aramid chopped fiber aqueous dispersion C obtained in (2) is paper-made on a 200-mesh forming net to obtain a loose, porous insulating paper substrate; the paper basis weight of the insulating paper substrate obtained is 8.2 g / m 2 ; (4) secondary forming and papermaking the para-aramid nanofiber aqueous dispersion B obtained in (1) on the insulating paper substrate obtained in (3) to obtain aramid nano insulating paper; (5) The aramid nano-insulating paper obtained in (4) is further pressed, dried, and hot-pressed to obtain tear-resistant aramid nano-insulating paper; the drying is carried out using a conventional papermaking process; the hot-pressing temperature is 230°C, the hot-pressing pressure is 11 MPa, and the hot-pressing time is 5 min; the mass ratio of para-aramid nanofibers to meta-aramid short fibers in the tear-resistant aramid nano-insulating paper is 80:20; the prepared paper has a basis weight of 41 g / m 2 .

[0021] Embodiment 3: A method for preparing tear-resistant aramid nano-insulating paper in this embodiment specifically comprises the following steps: (1) Para-aramid chopped fibers, potassium hydroxide, dimethyl sulfoxide and deionized water are mixed in proportion and sealed, and rapidly stirred at 1400 r / min for 3 h to obtain a para-aramid nanofiber dispersion with a concentration of 15 mg / mL; the diameter of the para-aramid nanofibers in the para-aramid nanofiber dispersion is 8-15 nm and the length is 3-8 μm; then, deionized water is injected into the para-aramid nanofiber dispersion under high pressure under the stirring action of 1300 r / min, and then washed with deionized water under vacuum filtration until it is in a gel state, to obtain a para-aramid nanofiber aqueous dispersion A dispersed in deionized water; the para-aramid nanofiber aqueous dispersion A is diluted, and then dispersed by dispersing stirring for 30000 r to obtain a para-aramid nanofiber aqueous dispersion B with a mass concentration of 0.08%; (2) Dispersing meta-aramid chopped short fibers: meta-aramid chopped medium and long fibers: meta-aramid chopped long fibers in water at a ratio of 30:40:30, adding a dispersant for dispersion, and then dispersing by stirring for 30,000 r to obtain a meta-aramid chopped fiber aqueous dispersion C with a mass concentration of 0.08%; (3) The meta-aramid chopped fiber aqueous dispersion C obtained in (2) is paper-made on a 200-mesh forming net to obtain a loose, porous insulating paper substrate; the paper basis weight of the insulating paper substrate obtained is 12.3 g / m 2 ; (4) secondary forming and papermaking the para-aramid nanofiber aqueous dispersion B obtained in (1) on the insulating paper substrate obtained in (3) to obtain aramid nano insulating paper; (5) The aramid nano-insulating paper obtained in (4) is further pressed, dried, and hot-pressed to obtain tear-resistant aramid nano-insulating paper; the drying is carried out using a conventional papermaking process; the hot-pressing temperature is 240°C, the hot-pressing pressure is 10 MPa, and the hot-pressing time is 8 min; the mass ratio of para-aramid nanofibers to meta-aramid short fibers in the tear-resistant aramid nano-insulating paper is 70:30; the prepared paper has a basis weight of 41 g / m 2 .

[0022] Embodiment 4: A method for preparing tear-resistant aramid nano-insulating paper in this embodiment specifically comprises the following steps: (1) Para-aramid chopped fibers, potassium hydroxide, dimethyl sulfoxide and deionized water are mixed in proportion and sealed, and rapidly stirred at 1500 r / min for 3.5 h to obtain a para-aramid nanofiber dispersion with a concentration of 10 mg / mL; the diameter of the para-aramid nanofibers in the para-aramid nanofiber dispersion is 8-15 nm and the length is 3-8 μm; then, deionized water is injected into the para-aramid nanofiber dispersion under high pressure under the stirring action of 1100 r / min, and then washed with deionized water under vacuum filtration until it is in a gel state, to obtain a para-aramid nanofiber aqueous dispersion A dispersed in deionized water; the para-aramid nanofiber aqueous dispersion A is diluted, and then dispersed by dispersing stirring for 20000 r to obtain a para-aramid nanofiber aqueous dispersion B with a mass concentration of 0.11%; (2) Dispersing meta-aramid chopped short fibers: meta-aramid chopped medium and long fibers: meta-aramid chopped long fibers in water at a ratio of 20:30:50, adding a dispersant for dispersion, and then dispersing by stirring for 20,000 r to obtain a meta-aramid chopped fiber aqueous dispersion C with a mass concentration of 0.09%; (3) The meta-aramid chopped fiber aqueous dispersion C obtained in (2) is paper-made on a 200-mesh forming net to obtain a loose, porous insulating paper substrate; the paper basis weight of the insulating paper substrate obtained is 16.4 g / m 2 ; (4) secondary forming and papermaking the para-aramid nanofiber aqueous dispersion B obtained in (1) on the insulating paper substrate obtained in (3) to obtain aramid nano insulating paper; (5) The aramid nano-insulating paper obtained in (4) is further pressed, dried, and hot-pressed to obtain tear-resistant aramid nano-insulating paper; the drying is carried out using a conventional papermaking process; the hot-pressing temperature is 245°C, the hot-pressing pressure is 12 MPa, and the hot-pressing time is 8 min; the mass ratio of para-aramid nanofibers to meta-aramid short fibers in the tear-resistant aramid nano-insulating paper is 60:40; the basis weight of the prepared paper is 41 g / m 2 .

[0023] Taking Example 4 as an example, first, the surface of the tear-resistant aramid nano-insulating paper prepared by the present invention is observed. FIG. 2(a) is a scanning electron microscope image of the surface of the aramid nano-insulating paper obtained in Example 4 of the present invention, and FIG. 2(b) is a partially enlarged scanning electron microscope image of the surface of the aramid nano-insulating paper obtained in Example 4 of the present invention. From the figure, we can clearly see that the aramid nano-fibers are tightly combined with the meta-aramid short fibers, and the aramid nano-fibers completely wrap the meta-aramid short fibers to form a dense aramid nano-network, which makes the surface of the paper smooth, increases the bonding force between the fibers, and improves the tearing degree of the paper. Secondly, the cross-section of the aramid nano-insulating paper is observed, as shown in FIG. Figure 3As shown in the figure, there is an obvious layered structure inside the paper. After hot pressing, the meta-aramid chopped fibers reach their glass transition temperature, the fibers soften and undergo slight deformation and migration, filling the gaps between the fibers and making the structure between the fibers dense. Finally, in order to verify its excellent dielectric properties, the aramid nano-insulating paper was subjected to an electrical breakdown test and its SEM image was observed. FIG4(a) is a scanning electron microscope image of the breakdown point of the aramid nano-insulating paper obtained in Example 4 of the present invention, and FIG4(b) is a locally enlarged scanning electron microscope image of the breakdown point of the aramid nano-insulating paper obtained in Example 4 of the present invention. It can be observed that dense carbon particles are generated around the breakdown site, and the structure is tight. Even after the breakdown, other parts of the insulating paper will not become loose.

[0024] Taking Example 4 as an example, the tear-resistant aramid nano-insulation paper prepared by the present invention was tested and the quantitative value was 41 g / m 2 , with an average thickness of 0.05 mm, a tear strength of 392 mN, and a dielectric strength of 36 kV / mm, which has excellent tear strength and dielectric strength. That is, the tear-resistant aramid nano-insulation paper has excellent mechanical and electrical properties, and has potential application value in large electrical equipment such as high-power dry-type transformers, oil-immersed transformers, special motors for mining, high-speed train traction motors, wind turbines, and ultra-high voltage transformers.

[0025] Embodiment 5: A method for preparing tear-resistant aramid nano-insulating paper in this embodiment specifically comprises the following steps: (1) Para-aramid chopped fibers, potassium hydroxide, dimethyl sulfoxide and deionized water are mixed in proportion and sealed, and rapidly stirred at 1300 r / min for 4 h to obtain a para-aramid nanofiber dispersion with a concentration of 10 mg / mL; the para-aramid nanofibers in the para-aramid nanofiber dispersion have a diameter of 8-15 nm and a length of 3-8 μm; then, deionized water is injected into the para-aramid nanofiber dispersion under high pressure under the stirring action of 1300 r / min, and then washed with deionized water under vacuum filtration until it is in a gel state, to obtain a para-aramid nanofiber aqueous dispersion A dispersed in deionized water; the para-aramid nanofiber aqueous dispersion A is diluted, and then dispersed by dispersing stirring for 30000 r to obtain a para-aramid nanofiber aqueous dispersion B with a mass concentration of 0.12%; (2) Dispersing meta-aramid chopped short fibers: meta-aramid chopped medium and long fibers: meta-aramid chopped long fibers in water at a ratio of 10:40:50, adding a dispersant for dispersion, and then dispersing by stirring for 30,000 r to obtain a meta-aramid chopped fiber aqueous dispersion C with a mass concentration of 0.1%; (3) The meta-aramid chopped fiber aqueous dispersion C obtained in (2) is paper-made on a 200-mesh forming net to obtain a loose, porous insulating paper substrate; the paper basis weight of the insulating paper substrate obtained is 20.5 g / m 2 ; (4) secondary forming and papermaking the para-aramid nanofiber aqueous dispersion B obtained in (1) on the insulating paper substrate obtained in (3) to obtain aramid nano insulating paper; (5) The aramid nano-insulating paper obtained in (4) is further pressed, dried, and hot-pressed to obtain tear-resistant aramid nano-insulating paper; the drying is carried out using a conventional papermaking process; the hot-pressing temperature is 235°C, the hot-pressing pressure is 15 MPa, and the hot-pressing time is 10 min; the mass ratio of para-aramid nanofibers to meta-aramid short fibers in the tear-resistant aramid nano-insulating paper is 50:50; the prepared paper has a basis weight of 41 g / m 2 .

[0026] Embodiment 6: A method for preparing tear-resistant aramid nano-insulating paper in this embodiment specifically comprises the following steps: (1) Para-aramid chopped fibers, potassium hydroxide, dimethyl sulfoxide and deionized water are mixed in proportion and sealed, and rapidly stirred at 1200 r / min for 4 h to obtain a para-aramid nanofiber dispersion with a concentration of 11 mg / mL; the diameter of the para-aramid nanofibers in the para-aramid nanofiber dispersion is 8-15 nm and the length is 3-8 μm; then, deionized water is injected into the para-aramid nanofiber dispersion under high pressure under the stirring action of 1500 r / min, and then washed with deionized water under vacuum filtration until it is in a gel state, to obtain a para-aramid nanofiber aqueous dispersion A dispersed in deionized water; the para-aramid nanofiber aqueous dispersion A is diluted, and then dispersed by dispersing stirring for 25000 r to obtain a para-aramid nanofiber aqueous dispersion B with a mass concentration of 0.06%; (2) Dispersing meta-aramid chopped short fibers: meta-aramid chopped medium and long fibers: meta-aramid chopped long fibers in water at a ratio of 10:50:40, adding a dispersant for dispersion, and then dispersing by stirring for 25000 r to obtain a meta-aramid chopped fiber aqueous dispersion C with a mass concentration of 0.11%; (3) The meta-aramid chopped fiber aqueous dispersion C obtained in (2) is paper-made on a 200-mesh forming net to obtain a loose, porous insulating paper substrate; the paper basis weight of the insulating paper substrate obtained is 9 g / m 2 ; (4) secondary forming and papermaking the para-aramid nanofiber aqueous dispersion B obtained in (1) on the insulating paper substrate obtained in (3) to obtain aramid nano insulating paper; (5) The aramid nano-insulating paper obtained in (4) is further pressed, dried, and hot-pressed to obtain tear-resistant aramid nano-insulating paper; the drying is carried out using a conventional papermaking process; the hot-pressing temperature is 245°C, the hot-pressing pressure is 14 MPa, and the hot-pressing time is 5 min; the mass ratio of para-aramid nanofibers to meta-aramid short fibers in the tear-resistant aramid nano-insulating paper is 70:30; the basis weight of the prepared paper is 30 g / m 2 .

[0027] Embodiment 7: A method for preparing tear-resistant aramid nano-insulating paper in this embodiment specifically comprises the following steps: (1) Para-aramid chopped fibers, potassium hydroxide, dimethyl sulfoxide and deionized water are mixed in proportion and sealed, and rapidly stirred at 1400 r / min for 3.5 h to obtain a para-aramid nanofiber dispersion with a concentration of 5 mg / mL; the diameter of the para-aramid nanofibers in the para-aramid nanofiber dispersion is 8-15 nm and the length is 3-8 μm; then, deionized water is injected into the para-aramid nanofiber dispersion under high pressure under the stirring action of 1400 r / min, and then washed with deionized water under vacuum filtration until it is in a gel state, to obtain a para-aramid nanofiber aqueous dispersion A dispersed in deionized water; the para-aramid nanofiber aqueous dispersion A is diluted, and then dispersed by dispersing stirring for 30000 r to obtain a para-aramid nanofiber aqueous dispersion B with a mass concentration of 0.1%; (2) Dispersing meta-aramid chopped short fibers: meta-aramid chopped medium and long fibers: meta-aramid chopped long fibers in water at a ratio of 20:50:30, adding a dispersant for dispersion, and then dispersing by stirring for 30,000 r to obtain a meta-aramid chopped fiber aqueous dispersion C with a mass concentration of 0.12%; (3) The meta-aramid chopped fiber aqueous dispersion C obtained in (2) is paper-made on a 400-mesh forming net to obtain a loose, porous insulating paper substrate; the paper basis weight of the insulating paper substrate obtained is 24 g / m 2 ; (4) secondary forming and papermaking the para-aramid nanofiber aqueous dispersion B obtained in (1) on the insulating paper substrate obtained in (3) to obtain aramid nano insulating paper; (5) The aramid nano-insulating paper obtained in (4) is further pressed, dried, and hot-pressed to obtain tear-resistant aramid nano-insulating paper; the drying is carried out using a conventional papermaking process; the hot-pressing temperature is 240°C, the hot-pressing pressure is 13 MPa, and the hot-pressing time is 9 min; the mass ratio of para-aramid nanofibers to meta-aramid short fibers in the tear-resistant aramid nano-insulating paper is 60:40; the basis weight of the prepared paper is 60 g / m 2 .

[0028] Embodiment 8: A method for preparing tear-resistant aramid nano-insulating paper in this embodiment specifically comprises the following steps: (1) Para-aramid chopped fibers, potassium hydroxide, dimethyl sulfoxide and deionized water are mixed in proportion and sealed, and rapidly stirred at 1500 r / min for 4 h to obtain a para-aramid nanofiber dispersion with a concentration of 10 mg / mL; the para-aramid nanofibers in the para-aramid nanofiber dispersion have a diameter of 8-15 nm and a length of 3-8 μm; then, deionized water is injected into the para-aramid nanofiber dispersion under high pressure under the stirring action of 1500 r / min, and then washed with deionized water under vacuum filtration until it is in a gel state, to obtain a para-aramid nanofiber aqueous dispersion A dispersed in deionized water; the para-aramid nanofiber aqueous dispersion A is diluted, and then dispersed by dispersing stirring for 20000 r to obtain a para-aramid nanofiber aqueous dispersion B with a mass concentration of 0.08%; (2) Dispersing meta-aramid chopped short fibers: meta-aramid chopped medium and long fibers: meta-aramid chopped long fibers in water at a ratio of 30:40:30, adding the PEO aqueous dispersion obtained above, and then dispersing by stirring for 20,000 hours to obtain a meta-aramid chopped fiber aqueous dispersion C with a mass concentration of 0.12%; (3) The meta-aramid chopped fiber aqueous dispersion C obtained in (2) is paper-made on a 300-mesh forming net to obtain a loose and porous insulating paper substrate; the paper basis weight of the insulating paper substrate obtained is 10 g / m 2 ; (4) secondary forming and papermaking the para-aramid nanofiber aqueous dispersion B obtained in (1) on the insulating paper substrate obtained in (3) to obtain aramid nano insulating paper; (5) The aramid nano-insulating paper obtained in (4) is further pressed, dried, and hot-pressed to obtain tear-resistant aramid nano-insulating paper; the drying is carried out using a conventional papermaking process; the hot-pressing temperature is 230°C, the hot-pressing pressure is 10 MPa, and the hot-pressing time is 10 min; the mass ratio of para-aramid nanofibers to meta-aramid short fibers in the tear-resistant aramid nano-insulating paper is 80:20, and the basis weight of the prepared paper is 50 g / m 2 .

[0029] Comparative Example 1: A method for preparing tear-resistant aramid nano-insulating paper in this embodiment specifically comprises the following steps: (1) Para-aramid chopped fibers, potassium hydroxide, dimethyl sulfoxide and deionized water are mixed in proportion and sealed, and rapidly stirred for reaction for 4 h to obtain a para-aramid nanofiber dispersion with a concentration of 10 mg / mL; the diameter of the para-aramid nanofibers in the para-aramid nanofiber dispersion is 8-15 nm and the length is 3-8 μm; then, deionized water is injected into the para-aramid nanofiber dispersion under high pressure while stirring, and then the para-aramid nanofiber dispersion is washed with deionized water under vacuum filtration until it is in a gel state, thereby obtaining a para-aramid nanofiber aqueous dispersion A dispersed in deionized water; the para-aramid nanofiber aqueous dispersion A is diluted, and then dispersed in a deflaker by deflaking and stirring for 20,000 r to obtain a para-aramid nanofiber aqueous dispersion B; (2) The para-aramid nanofiber dispersion B obtained in (1) is diluted to a mass concentration of 0.1%, and then papered on a 500-mesh forming net, pressed, and dried to obtain aramid nanopaper; the pressing and drying are both carried out using conventional papermaking processes.

[0030] (3) The aramid nanopaper obtained in (2) is subjected to hot pressing to obtain aramid nano-insulating paper; the hot pressing temperature is 240°C, the hot pressing pressure is 12 MPa, and the hot pressing time is 5 min.

[0031] The performance analysis and testing standards for the aramid nano-insulating paper samples of Examples 2-7 and Comparative Example 1 of the present invention are as follows: The tear strength of paper samples is based on GB / T 455-2002 “Determination of tear strength of paper and paperboard”.

[0032] The tear strength of the aramid nano insulating paper prepared in comparative example 1 is only 20 mN, while the tear strength of the aramid nano insulating paper prepared by embodiments 2-7 of the technical solution of the present invention is 251-577 mN, which is 13-29 times higher than that of comparative example 1.

[0033] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing tear-resistant aramid nano-insulation paper, characterized in that: The steps include: S1, preparing a para-aramid nanofiber aqueous dispersion: injecting deionized water into a para-aramid nanofiber dispersion in a system of dimethyl sulfoxide, potassium hydroxide and deionized water under high pressure while stirring, and then washing with deionized water under vacuum filtration until it is in a gel state, thereby obtaining a para-aramid nanofiber aqueous dispersion A dispersed in deionized water; diluting the para-aramid nanofiber aqueous dispersion A, and then dispersing by dispersing and stirring to obtain a para-aramid nanofiber aqueous dispersion B; S2, preparing a meta-aramid chopped fiber aqueous dispersion: dispersing meta-aramid chopped fibers of different lengths in water, adding a dispersant, and then dispersing by dispersing and stirring to obtain a meta-aramid chopped fiber aqueous dispersion C; S3, papermaking the meta-aramid chopped fiber aqueous dispersion C obtained in S2 to obtain a loose and porous insulating paper matrix; the basis weight of the insulating paper matrix is ​​3-30 g / m 2 ; S4, the para-aramid nanofiber aqueous dispersion B obtained in S1 is subjected to secondary forming and papermaking on the insulating paper substrate obtained in S3 to obtain aramid nano-insulating paper; the aramid nano-insulating paper has a basis weight of 30-60 g / m 2 , wherein the mass ratio of para-aramid nanofiber to meta-aramid short-cut fiber is 50~90:10~50; S5, further squeezing, drying, and hot-pressing the aramid nano-insulation paper obtained in S4 to obtain tear-resistant aramid nano-insulation paper.

2. The method for preparing tear-resistant aramid nano-insulation paper according to claim 1, characterized in that: The preparation method of the para-aramid nanofiber dispersion in the dimethyl sulfoxide, potassium hydroxide and deionized water system in S1 is: para-aramid chopped fibers, potassium hydroxide, dimethyl sulfoxide and deionized water are mixed in proportion and sealed, and then stirred and reacted at a speed of 1200-1500 r / min for 2-4 hours to obtain a para-aramid nanofiber dispersion with a concentration of 5-15 mg / mL; the diameter of the para-aramid nanofibers in the para-aramid nanofiber dispersion is 8-15 nm, and the length is 3-8 μm.

3. The method for preparing tear-resistant aramid nano-insulation paper according to claim 1, characterized in that: In the S1, the para-aramid nanofiber dispersion in the dimethyl sulfoxide, potassium hydroxide and deionized water system is stirred at a speed of 1000-1500 r / min.

4. The method for preparing tear-resistant aramid nano-insulation paper according to claim 1, characterized in that: In the S1, the para-aramid nanofiber aqueous dispersion A is dispersed and stirred for 20000-30000 r; the mass concentration of the para-aramid nanofiber aqueous dispersion B is 0.05-0.12%.

5. The method for preparing tear-resistant aramid nano-insulation paper according to claim 1, characterized in that: The ratio of the meta-aramid short fibers of different lengths in S2, calculated by weight, is 10~30:30~50:30~50 for meta-aramid short fibers:30~50 for meta-aramid short fibers; the length of the meta-aramid short fibers is 4~6 mm, the length of the meta-aramid short fibers is 7~9 mm, and the length of the meta-aramid short fibers is 10~12 mm.

6. The method for preparing tear-resistant aramid nano-insulation paper according to claim 1, characterized in that: The S2 is dispersed by stirring for 20000-30000 r; the mass concentration of the meta-aramid chopped fiber aqueous dispersion C is 0.05-0.12%.

7. The method for preparing tear-resistant aramid nano-insulation paper according to claim 1, characterized in that: The S3 is specifically as follows: papermaking the meta-aramid chopped fiber aqueous dispersion C obtained in S2 on a 200-400 mesh forming net to obtain a loose and porous insulating paper matrix.

8. The method for preparing tear-resistant aramid nano-insulation paper according to claim 1, characterized in that: The pressing and drying in S5 are both carried out using conventional papermaking processes, with a hot pressing temperature of 230-245° C., a hot pressing pressure of 10-15 MPa, and a hot pressing time of 5-10 min.

9. A tear-resistant aramid nano-insulation paper, characterized in that: The invention is obtained based on the preparation method of the tear-resistant aramid nano insulating paper described in any one of claims 1 to 8.

10. Application of the tear-resistant aramid nano-insulation paper according to claim 9 in the field of next-generation highly lightweight and integrated special electrical equipment.

Citation Information

Patent Citations

  • Composite papermaking nano reinforced aramid paper and preparation method thereof

    CN112609493A

  • Preparing method of water-dispersed aramid nanofiber and aramid nanopaper

    CN108285540A

  • Gradient-structure nanometer aramid paper making method

    CN109468882A

  • Aramid fiber modification method

    CN113389080A

  • Process for preparing immersive insulating aramid paperboard by using inertia

    CN114703694A